Risk factors in young adults for the development of cardiovascular disease: what does the literature show? - Menezes, João Daniel de Souza (2021)
Introduction: Cardiovascular diseases represent a major burden to public health, are the leading cause of death worldwide and have generated loss of quality of life, limitations in work and leisure activities, in addition to economic impacts to families and society in general. Although it is recognized that cardiovascular diseases and hypertension are more commonly seen in individuals in adulthood, the manifestation of these diseases results from the interaction of risk factors acquired at a young age. Objective: The present study aimed to evaluate the risk factors associated with the development of cardiovascular diseases in young adults. Methodology: A review of studies on risk factors for hypertension and heart disease in young adults was conducted in the PubMed/Medline, Lilacs and Scielo databases. There was no restriction as to the language used in the publications. The search was conducted in April 2021, using the descriptors "risk factors," "cardiovascular diseases," "young adults," and "hypertension." Results: Based on the studies addressed, the risk of cardiovascular diseases and hypertension may begin as early as the first decades of life, given that adolescents and individuals at a young age make up an important vulnerable group to situations of exposure to risk factors for the development of harmful cardiovascular events, with emphasis on those related to lifestyle such as sedentarism, alcoholism, smoking, poor adherence to regular physical activity and increased body mass index by a diet based on high caloric density. Conclusions: The studies highlight the importance of delineating the risk factors early in life associated with the development of cardiovascular disease and hypertension that can focus and inform preventive measures or facilitate the adoption of approaches that promote healthy behaviors and attitudes throughout life.